Penggunaan Media Buku Halo Balita dalam Pembentukan Karakter Religius Anak Usia Prasekolah - Titi Rachmi; Diah Retno Anggraini; Yufiarti Yufiarti (Jurnal Psikologi Islam dan Budaya, 2021)
The aim of this study was to describe the process of interpreting the book Halo Balita with activities and learning programs to build religious characters in preschool children. This research used qualitative methods, data was collected by using observation and interview with 5 primary subject preschool children, and 35 secondary subjects of parents. Data was analyzed by NVivo 12 Plus application to explore religious beliefs, worships, religious knowledge and experiences. The result of this study describes the book Halo Balita can help create and built religious characters of preschool children through activites before, during and after using the book Halo Balita with daily activities, that is when conducting activities inside and outside the classroom, as well as activites undertaken in the family and community environment so that it becomes more independent, caring, honest, and has beliefs related to understanding the creed.